2021
DOI: 10.21203/rs.3.rs-357905/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Air Quality Forecasting with Hybrid LSTM and Extended Stationary Wavelet Transform

Abstract: Artificial intelligence (AI) technology-enhanced air quality forecasting is one of the most promising directions in the field of smart environment development. Despite recent advances in this area, two difficulties remain unsolved. First, multiple factors influence forecasting results, such as weather conditions, fuel usage and traffic conditions. These factors are usually unavailable in air quality sensor data. Second, traditional predicting models typically use the most recent training data, which neglects t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Using the extended a (NLSTM) neural network, Zeng et al [16] suggested a new forecasting model for PM2.…”
Section: Related Workmentioning
confidence: 99%
“…Using the extended a (NLSTM) neural network, Zeng et al [16] suggested a new forecasting model for PM2.…”
Section: Related Workmentioning
confidence: 99%